Coal as a non-conventional resource of rare earth elements (REEs) and trace elements: Benefits and impacts on environment and human health – A review - Himanshu Jaiswal; Alok K. Singh (Results in Earth Sciences)
In the current scenario of increasing demands for electronic gadgets, electric vehicles, permanent magnets, renewable energy, and defense industries, the need for REEs has grown exponentially. China controls the REEs market globally, and this global dependency has created political insecurity and concerns regarding the stability of the REE market. Carbonatite and Per-alkaline rocks are the conventional sources of REEs, but their worldwide abundance is minimal. Coal, for instance, consists of organic and inorganic components, with the inorganic part associated with the most REEs, such as ash, having minimal utilization and posing challenges. Extracting REEs from coal ash allows one to convert waste into a valuable resource, aligning with the concept of ''waste to wealth.'' Traditional REEs extraction methods involve harsh acids, posing significant risks to environmental and living organisms. Therefore, there is an urgent need to explore innovative and sustainable extraction methods for REEs, particularly utilizing non-conventional sources. To achieve this, it is necessary to develop equipment that can be installed in thermal power plants during the final stage of thermal processing, enabling the extraction of REEs from the same plants to make the thermal plants more beneficial and add value to already running thermal plants. Finally, it mitigates groundwater, soil leaching, and atmospheric pollution associated with the presence of these elements in coal ash. By successfully extracting REEs from ash, the profitability of the thermal industry can be enhanced as it transforms thermal plants from operating at marginal profits to generating additional revenue streams.